Design Dan Implementasi Sistem Informasi Apotek Pada Apotek Mitra Agung Pacitan - Prihantara, Aditya; Riasti, Berliana Kusuma (Speed - Sentra Penelitian Engineering dan Edukasi, 2012)
Pharmacy is a venue drug information services and other pharmaceutical supplies to the public. Today has been a lot of pharmacies are standing and spreading to rural areas making it easier for people to access pharmaceutical equipment and drugs. Pacitan General Partner Pharmacies for this is still using the conventional way in the sale and purchase of drugs, data inventory and report to the leadership, so that the implementation is very difficult for the performance of cashiers and pharmacists. In addition the use of conventional ways that are also caused an error in reporting on the condition of the company to the leadership, which led to errors in decision making. This study aims at providing an efficient pharmacy information system and appropriate in order to support the performance of the pharmacy itself. Pharmacy information system has a set of management functions of the pharmacy in terms of the sale and purchase transaction records of drugs, inventory, and report to the leadership, good cashier reports, stock reports and profit and sales. Data collection methods used in this study is observation, interview and literature studies, then implemented using the programming language PHP and the MySQL database. It is expected that the system built will actually be able to overcome the problems posed by the old ways are still conventional.